2013
DOI: 10.1002/app.39467
|View full text |Cite
|
Sign up to set email alerts
|

Impact of p‐toluenesulfonate on polypyrrole–cobalt catalyst for oxygen reduction reaction

Abstract: Polypyrrole (PPy) and polypyrrole p-toluenesulfonate (PPy/pTS) supported cobalt (Co) catalysts have been synthesized using in situ surfactant modified chemical oxidative polymerization. These catalysts have been characterized for their structure and electrocatalytic activity employing FT-IR, Raman, SEM, HRTEM, and electrochemical techniques. The influence of pTS on the morphology and oxygen reduction reaction (ORR) activity has been discussed in respect of the formation of polaronic and bipolaronic species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…碳负载的Pt及其 合金催化剂具有最好的ORR活性, 近来人们还论证了纳 米尺寸的金颗粒在碱性电解质中具有非常好的ORR活 性 [12] , 但是Pt和Au的价格昂贵. 在非贵金属的ORR催化 剂中, Fe和Co基催化剂 [13][14][15][16] 在酸性介质中具有较好的 ORR活性, 而 Mn 氧化物 [17,18] 、钙钛矿 [19,20] 以及尖晶 石 [21,22] 在碱性介质中具有较好的ORR活性, 此外,部分 Fe基催化剂在碱性电解质中也具有很好的ORR活性 [23] .…”
Section: 前言unclassified
See 1 more Smart Citation
“…碳负载的Pt及其 合金催化剂具有最好的ORR活性, 近来人们还论证了纳 米尺寸的金颗粒在碱性电解质中具有非常好的ORR活 性 [12] , 但是Pt和Au的价格昂贵. 在非贵金属的ORR催化 剂中, Fe和Co基催化剂 [13][14][15][16] 在酸性介质中具有较好的 ORR活性, 而 Mn 氧化物 [17,18] 、钙钛矿 [19,20] 以及尖晶 石 [21,22] 在碱性介质中具有较好的ORR活性, 此外,部分 Fe基催化剂在碱性电解质中也具有很好的ORR活性 [23] .…”
Section: 前言unclassified
“…Recently, the nano Au particles have shown good ORR catalytic performance in alkaline medium [12], but Pt and Au are similarly very expensive. Among non-precious metal catalysts for the ORR, Fe-and Co-based catalysts [13][14][15][16] exhibit good activity in an acidic medium, while Mn oxides [17,18], perovskites [19,20], and spinels [21,22] have good ORR activity in an alkaline medium. However, it also has been demonstrated that Fe-based catalyst is also active toward ORR in alkaline medium [23].…”
Section: Introductionmentioning
confidence: 99%